Differences in Unemployment due to Sexual Orientation: Evidence from the Swedish Labour Market - Can Karaarslan (Hochschule Offenburg, Fakultät Medien, 2021)
The right to engage in work and choose an occupation to freely work at, is declared a fundamental human right in the EU. Behaviour that restrains somebody from doing so, due to sexual orientation discrimination for example, is prohibited. Inquiries on the dimension of this particular behaviour, as well as the magnitude of harm it causes in the population, is of vital importance for policy makers and the entire civil society. A growing number of research pertaining to labour market outcomes due to sexual orientation has been conducted rececently. Most of the studies have been carried out in western countries, where annual income, hourly wages, labour market participation and employment decisions have been in the focus of researchers. Ahmet, Andersson and Hammarstedt have been the pioneering scientists in this field in Sweden and contributed by extending their inquiries from the individual to the couple level (Ahmed, et al., 2011a) and to field experiments (Ahmed, et al., 2011b) in detecting discrimination against homosexuals. The present paper aims to contribute to the labour market discrimination literature by estimating the differences in the employment probabilities and in the duration of unemployment by sexual orientation in Sweden using survival analysis techniques. Time-to-event data is rare in social sciences, which is particularly valid for data sets where the sexual orientation of individuals is observable. Due to this scarcity, the present study represents the first paper investigating the effect of sexual preferences on the duration in unemploymnet using survival analysis techniques. In contrast to other estimation methods, survival techniques enable us to incorporate the particular nature of time-to-event data, such as its particular skewness, strict non- negative nature, as well as censoring and truncation. Separately Zero Inflated Negative Binomial regression has been conducted to the duration in unemployment and Probit estimation to the event of getting employed, where differing significant outcomes by sexual orientation have been detected for some specifications. The remainder of the article is organized as follows. A detailed literature review is provided in section 2. Section 3 comprises the theoretical framework of the investigation, while section 4 contains the methodical framework and research design. Data and descriptive statistics are presented in section 5, followed by the results of the estimation in section 6. Section 7 concludes with the final discussion.
urn:nbn:de:bsz:ofb1-opus4-49911
Keywords: 330; Sexual Orientation; Unemployment